ESTHETIC MANAGEMENT OF GUMMY SMILE VIA GINGIVECTOMY - Giacomo Gobbo Trojan; Victoria Carminatti Silveira; Amanda Jaime Ricci; Camila Aparecida da Silva Cavalini; Danielle Vitor Pimenta; Thaynara Laila de Souza (International Journal of Health Management Review, 2026)
A gummy smile is characterized by excessive gingival display while smiling and has a multifactorial etiology, potentially involving altered passive eruption, lip hypermobility, and vertical maxillary excess. This study aimed to analyze gingivectomy as an aesthetic approach for correcting a gummy smile through a narrative literature review conducted using the PubMed database. The analyzed studies demonstrate that gingivectomy—whether performed alone or in conjunction with gingivoplasty and clinical crown lengthening—yields satisfactory results when correctly indicated. The procedure's success depends on accurate diagnosis, individualized planning, respect for biological width, and the maintenance of gingival proportion and symmetry. Tools such as mock-ups, surgical guides, and diode lasers can contribute to greater precision and postoperative comfort. In this context, gingivectomy stands out as an effective and predictable alternative for correcting a gummy smile, provided that the decision to perform it takes into account each patient's periodontal, dental, labial, and facial characteristics.